Pemanfaatan Tar Residu Bio-Oil Limbah Tempurung Kelapa dengan Aditif Biochar dan Gondorukem Menjadi Bio-Aspal - Afrah, Bazlina Dawami; Delli Saputri, Jasmine Fadhilah; Ramona Putri, Tiara Maharani; Ihsan Riady, Muhammad; Muzzaki, Ahmad Nabil (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Indonesia still faces critical infrastructure issues, especially in road maintenance, with 31.9% of roads damaged and 15.9% severely damaged in 2021. It caused by the high production costs to achieve the best asphalt quality and the dwindling availability of petroleum raw materials. Without action, this could worsen infrastructure and disrupt connectivity, requiring a timely and effective solution. Therefore, there is a need for alternative renewable materials and simple methods of production. This research aims to obtain a bio-asphalt product that can compete with oil asphalt, using the main ingredient of tar (bio-oil) from coconut shell pyrolysis as well as additives in the form of biochar and gondorukem. This research was conducted through three stages: pyrolysis, distillation, and mixing. The pyrolysis stage was carried out at a temperature range of 300-400oC to obtain bio-oil. The distillation stage is carried out at 250oC to obtain tar. The mixture consists of 30% tar and 70% petroleum asphalt. The variations used are the type of additive and the percentage composition of the additive so that the most optimal bio-asphalt formulation is obtained. The Bio-asphalt superior product almost meets the five existing parameters, with a penetration value of 60/70, ductility of 132.33 mm, soft point of 52.8oC and flash point of 254oC, the specific gravity that does not meet is 0.965 gr/cc. Therefore, this research is a solution in the production of economical asphalt so that the welfare of an evenly distributed society in the field of infrastructure can be achieved.